2021
DOI: 10.1093/tas/txab053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of providing artificial shade to pregnant grazing beef heifers on vaginal temperature, growth, activity, and behavior

Abstract: This experiment evaluated the effects of providing artificial shade during summer on activity, behavior, and growth performance of pregnant grazing beef heifers. Thirty-six black-hided Angus and Angus crossbred pregnant heifers [418 ± 9 kg body weight (BW); approximately 90 d of gestation] were stratified by breed, blocked by BW, and allocated to 12 ‘Pensacola’ bahiagrass pastures (Paspalum notatum Flüggé; 1.3 ha, n = 3 heifers/pasture) with or without access to artificial shade (SHADE vs. NO SHADE; 6 pastures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…With an impact on BW of Brangus heifers, which were the lightest at weaning and at 14-d post-weaning. In our previous study [ 8 ] we demonstrated that heifers grazing warm-season forages with access to an artificial shade, gained 0.2 kg/d, whereas heifers without shade lost 0.02 kg/d. Enhanced growth performance for grazing beef heifers has been reported by Monn et al [ 22 ], who observed an increase of 0.2 kg/d for beef heifers with access to shade compared to cows with no access to shade.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…With an impact on BW of Brangus heifers, which were the lightest at weaning and at 14-d post-weaning. In our previous study [ 8 ] we demonstrated that heifers grazing warm-season forages with access to an artificial shade, gained 0.2 kg/d, whereas heifers without shade lost 0.02 kg/d. Enhanced growth performance for grazing beef heifers has been reported by Monn et al [ 22 ], who observed an increase of 0.2 kg/d for beef heifers with access to shade compared to cows with no access to shade.…”
Section: Discussionmentioning
confidence: 98%
“…When cattle are unable to effectively dissipate heat for the maintenance of homeothermy, body temperature rises [ 18 ]. The provision of shade is associated with reductions in body temperature in beef and dairy cattle [ 8 , 19 22 ]. However, in the current study, Brangus and Angus cows with access to shade had similar vaginal temperatures compared to cows without access to shade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tympanic temperature determination has been performed with good results in dairy cattle (Jara et al 2016;Shu et al 2021). The relationship of physiological responses of animals varies according to the ecological zone and their respective climate conditions (Silva et al 2021). This observation reinforces the need to evaluate the animal's response to particular productive scenarios to analyze adaptive processes and keep contributing to study the associations between climate and milk production under grazing conditions, especially in tropical areas where this activity has been showing a sustained growth and offers an agribusiness opportunity for its population in the coming years.…”
Section: Introductionmentioning
confidence: 99%